2019
DOI: 10.1186/s12989-019-0324-2
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaled gold nanoparticles cause cerebral edema and upregulate endothelial aquaporin 1 expression, involving caveolin 1 dependent repression of extracellular regulated protein kinase activity

Abstract: BackgroundGold nanoparticles (Au-NPs) have extensive applications in electronics and biomedicine, resulting in increased exposure and prompting safety concerns for human health. After absorption, nanoparticles enter circulation and effect endothelial cells. We previously showed that exposure to Au-NPs (40–50 nm) collapsed endothelial tight junctions and increased their paracellular permeability. Inhaled nanoparticles have gained significant attention due to their biodistribution in the brain; however, little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that AuNPs alleviate inflammatory response and tight junction proteins via several signaling pathways including the NF-κB and ERK/JNK pathways [23,[39][40][41]. In detail, AuNPs protected against Aβ-induced neuroinflammation and neurodegeneration by targeting the NF-κB/JNK/glycogen synthase kinase 3β (GSK3β) signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that AuNPs alleviate inflammatory response and tight junction proteins via several signaling pathways including the NF-κB and ERK/JNK pathways [23,[39][40][41]. In detail, AuNPs protected against Aβ-induced neuroinflammation and neurodegeneration by targeting the NF-κB/JNK/glycogen synthase kinase 3β (GSK3β) signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of AQP-1 expression leads to aggravation of edema, whereas upregulation of AQP-1 expression alleviates acute pulmonary edema . Chen et al demonstrated that gold nanoparticle-mediated AQP-1 induction is dependent on caveolin-1, but it requires the repression of ERK activity …”
Section: Introductionmentioning
confidence: 99%
“…9 Chen et al demonstrated that gold nanoparticle-mediated AQP-1 induction is dependent on caveolin-1, but it requires the repression of ERK activity. 10 Intercellular transport mediated by tight, adherent, and gap junctions is the main mechanism for endothelial intercellular permeability. Occludin, claudin-5, and zonula occludens 1 (ZO-1) are the key components of a tight junction; the downregulation of the tight-junction protein regulated inflammatory signal transduction and lung endothelial permeability during lung injury.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotoxicological studies with ENM in rodents have been performed with the most widely produced and used materials like Ag, SiO 2 , TiO 2 , CeO 2 , ZnO and carbon black. However, also less common materials have been studied like gold, quantum dots or iridium nanoparticles (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%